2022
DOI: 10.3390/nu14235027
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Circulating Human Metabolites from Fish Cartilage Hydrolysate on Primary Human Dermal Fibroblasts, an Ex Vivo Clinical Investigation for Skin Health Applications

Abstract: Due to its significant exposure to stressful environmental factors, the skin undergoes a high remodeling rate over time, which alters not only its appearance but also its functionality. This alteration of the skin, namely photoaging, is characterized by dryness and a loss of elasticity that mainly originates from the dysregulation of dermal fibroblast activities. In order to overcome such tissue outcome, cosmetic products have evolved toward nutricosmetics, thus promoting beauty from within. Among bio-actives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our precedent study demonstrated the beneficial effects of FCH for nutricosmetic applications, by supporting hydration, elasticity and limiting the expression of catabolic factors involved in photoaging [19]. Here, we studied whether FCH could promote the healing process, using a mimicking fibroblast lesion in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our precedent study demonstrated the beneficial effects of FCH for nutricosmetic applications, by supporting hydration, elasticity and limiting the expression of catabolic factors involved in photoaging [19]. Here, we studied whether FCH could promote the healing process, using a mimicking fibroblast lesion in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the human serum enriched with circulating metabolites resulting from FCH ingestion (FCH-enriched serum), stimulated the growth of human dermal fibroblasts (HDFs), promoted the specific production of hyaluronan, up-regulated the synthesis of elastin and inhibited the expressions of matrix metalloproteinases (MMP)-1 and 3 along with an increase in TGF-β release. Thus, FCH promotes hydration, elasticity and limits the expression of catabolic factors involved in photoaging [19]. Additionally, it was previously showed that supplementation of middle-aged healthy women with this FCH led to both, a significant reduction in wrinkles and an increase of dermis density [20].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Relevance and robustness of such an ex vivo clinical trial were initially validated by Wittrant’s group [ 28 , 29 , 30 , 31 , 32 , 33 ]. A sample size of 10 subjects was hypothesized to detect a minimum effect size of 1, with a two-sided 5% significance level and a power of 90%.…”
Section: Methodsmentioning
confidence: 99%
“…To address both of these knowledge gaps and to contribute to the understanding of saffron's mechanisms in humans, in particular in chronic inflammation diseases, we designed an ex vivo approach combining human serum compounds derived from the intake of a saffron extract and cell cultures and evaluated in this study whether these human circulating bioactives may influence the response to inflammatory stress in chondrocytes and intestine epithelial cells. Relevance and robustness of such an ex vivo clinical trial were initially validated by Wittrant's group [28][29][30][31][32][33]. A sample size of 10 subjects was hypothesized to detect a minimum effect size of 1, with a two-sided 5% significance level and a power of 90%.…”
Section: Introductionmentioning
confidence: 99%